EnVi: Energy Efï¬cient Video Player for Mobiles - Suneja, Sahil; Navda, Vishnu; Ramjee, Ramachandran; Lara, Eyal de (CellNet 2013 workshop, 2013)
Watching online movies and TV shows while on the go is rapidly becoming one of the most common uses of smartphone. Unfortunately, sustained use of the cellular interface for long-standing data transfers severely reduces the battery life of the device. This paper introduces EnVi, a signal-aware scheduler that saves energy for mobile downloads by scheduling data transfers when signal quality is expected to be good, and avoiding communication in other periods. EnVi uses a self-calibrating approach that does not require assistance from the network, or knowledge of the user's route and future signal profile. EnVi is robust to signal profile changes due to time of day effects, different cell tower associations and new cell tower deployments. In a preliminary evaluation on a suburban train route, our EnVi video player achieved average radio energy savings of 20.7%, going up to as high as 32.5%.